The politics of lists : bureaucracy and genocide under the Khmer Rouge - Tyner, James A. 1966- (Morgantown : West Virginia University Press, 2018)
"The Politics of Lists analyzes thousands of newly available Cambodian documents both as sources of information and as objects worthy of study in and of themselves. How, Tyner asks, is recordkeeping implicated in the creation of political authority? What is the relationship between violence and bureaucracy? How can documents, as an anonymous technology capable of conveying great force, be understood in relation to newer technologies like drones? What does data create and what does it destroy? Through a theoretically informed, empirically grounded study of the Khmer Rouge security apparatus, Tyner shows that lists and telegrams have often proved as deadly as bullet and bombs"
Emerging from the shadows -- A tale of two lists -- Into the darkness -- Mortal accountings
Includes bibliographical references (pages 219-236) and index
Keywords: Government information -- History -- 20th century -- Cambodia; Bureaucracy -- History -- 20th century -- Cambodia; Genocide -- History -- 20th century -- Cambodia; Cambodia -- Politics and government -- 1975-1979